Emerging Role of Epigenetic Mechanisms in Alcohol Addiction - Berkel, Tiffani D.M.; Pandey, Subhash C. (Alcoholism, clinical and experimental research, 2017)
Alcohol use disorder (AUD) is a complex brain disorder with an array of persistent behavioral and neurochemical manifestations. Both genetic and environmental factors are known to contribute to the development of AUD, and recent studies on alcohol exposure and subsequent changes in gene expression suggest the importance of epigenetic mechanisms. In particular, histone modifications and DNA methylation have emerged as important regulators of gene expression and associated phenotypes of AUD. Given the therapeutic potential of epigenetic targets, this review aims to summarize the role of epigenetic regulation in our current understanding of AUD by evaluating known epigenetic signatures of brain regions critical to addictive behaviors in both animal and human studies throughout various stages of AUD. More specifically, the effects of acute and chronic alcohol exposure, tolerance, and postexposure withdrawal on epigenetically induced changes to gene expression and synaptic plasticity within key brain regions and the associated behavioral phenotypes have been discussed. Understanding the contribution of epigenetic regulation to crucial signaling pathways may prove vital for future development of novel biomarkers and treatment agents in ameliorating or preventing AUD. The epigenetic influence on synaptic plasticity appears to be instrumental in the development of alcoholism via histone deacetylase (HDAC)‐induced chromatin remodeling. Aberrant DNA methylation mechanisms are also important in regulating expression of various genes and associated biological pathways during alcoholism. Stratification of subjects by alcohol use disorder (AUD) phases is useful as epigenetic mechanisms uniquely regulate acute exposure/binge‐drinking, post‐dependence, and withdrawal effects. HDAC and DNA methyltransferase (DNMT) inhibitors consistently attenuate AUD phenotypes, and histone methyltransferase (HMT) inhibitors warrant exploration.